Description of two new species of Ampulicomorpha (Hymenoptera Embolemidae) (Bollettino di zoologia agraria e bachicoltura, 2024)
Ampulicomorpha madecassa n. sp. from Madagascar and A.costaricana n. sp. from Costa Rica are described. A new key to the world speciesof the genus Ampulicomorpha Ashmead 1893 is given.
Keywords: Taxonomy; new species; Ampulicomorpha madecassa; Ampulicomorpha costaricana